Probing and Controlling Intragrain Crystallinity for Improved Low Temperature-Processed Perovskite Solar Cells - James Durrant (Advanced Functional Materials, 2018)
Here, previously unobserved nanoscale defects residing within individual grains of solution‐processed methylammonium lead tri‐iodide (CH3NH3PbI3, MAPI) thin films are identified. Using scanning transmission electron microscopy (STEM), the defects inherently associated with the established solution‐processing methodology are identified, and a facile processing modification to eliminate these defects is introduced. Specifically, defect elimination is achieved by coannealing the as‐deposited MAPI layer with the electron transport layer (phenyl‐C61‐butyric acid methyl, PCBM) resulting in devices that significantly outperform devices prepared using the established methodology—with power conversion efficiencies increasing from 13.6% to 17.4%. The use of transmission electron microscopy allows the correlation of performance enhancements to improved intragrain crystallinity and shows that highly coherent crystallographic orientation results within individual grains when processing is modified. Detailed optoelectronic characterization reveals that the improved intragrain crystallinity drives an improvement of charge collection and a reduction of PEDOT:PSS/perovskite interfacial recombination. The study suggests that the microstructural defects in MAPI, owing to a lack of structural coherence throughout the thickness of thin film, are a significant cause of interfacial recombination.